Budgeting, strategic planning and institutional diversity in higher education. Issue 9 (2nd September 2021) - Kenno, Staci; Lau, Michelle; Sainty, Barbara; Boles, Bryan
ABSTRACT: This study investigates the systematic, structural, procedural and reputational differences associated with the use of budgeting for strategic planning across public sector institutions in Canada. Data obtained from a survey of 38 universities across Canada along with publicly available hand-collected data supports a heterogenous mix of budgeting practices across higher education. Our results show institutions rely on budgeting for multiple reasons including control, strategic planning, communication, and regulatory compliance. The findings indicate the adoption of performance management by some institutions, but not others based on systematic differences including budget model, institutional size, decentralization and reputation. The results support a contingency perspective of organizational practices in higher education.